2022
DOI: 10.2807/1560-7917.es.2022.27.6.2001953
|View full text |Cite
|
Sign up to set email alerts
|

Early chains of transmission of COVID-19 in France, January to March 2020

Abstract: Introduction SARS-CoV-2, the virus that causes COVID-19, has spread rapidly worldwide. In January 2020, a surveillance system was implemented in France for early detection of cases and their contacts to help limit secondary transmissions. Aim To use contact-tracing data collected during the initial phase of the COVID-19 pandemic to better characterise SARS-CoV-2 transmission. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Our results also showed a different distribution by age group, with higher seroprevalence in older individuals, particularly those aged 60-69 years and >70 years (18.6% and 18.0%, respectively). In France, during the first wave, the risk of becoming a case was higher for contacts aged 60-74 years (adjusted odds ratio-AOR: 2.0, 95% CI: 1.2-3.3), and older than 75 years (AOR: 2.1, 95% CI: 1.1-3.9), compared with the reference group of 15-29 years [32]. Further relevant data concerned the high seroprevalence of individuals aged <20 years (17.1%).…”
Section: Discussionmentioning
confidence: 94%
“…Our results also showed a different distribution by age group, with higher seroprevalence in older individuals, particularly those aged 60-69 years and >70 years (18.6% and 18.0%, respectively). In France, during the first wave, the risk of becoming a case was higher for contacts aged 60-74 years (adjusted odds ratio-AOR: 2.0, 95% CI: 1.2-3.3), and older than 75 years (AOR: 2.1, 95% CI: 1.1-3.9), compared with the reference group of 15-29 years [32]. Further relevant data concerned the high seroprevalence of individuals aged <20 years (17.1%).…”
Section: Discussionmentioning
confidence: 94%
“…The positive findings from studies that performed GS and phylogenetic analysis with identical strains supports the hypothesis that SARS-CoV-2 transmission occurs in close contact settings. The routes of transmission are unclear but may include direct and indirect contact and/or large droplet or short-range aerosol transmission as possible explanations for the identified identical strains in close contacts [3][4][5] . The failure of the majority of studies to report Ct values casts doubts on the strengths of any reported associations because of the likelihood of false positives, as is the lack of (and variation in) reporting of the timelines for sample collections.…”
Section: Summary Of Main Findingsmentioning
confidence: 99%
“…Helsingen 2020 3 Paireau 2020 4 Kuwelker 2020 5 Lyngse 2020 6 Jones 2020 7 Chen 2020 8 Fontanet 2020 9 Armann 2020 10 Charlotte 2020 11 Angulo-Bazan 2020 12…”
Section: Study Idmentioning
confidence: 99%
See 2 more Smart Citations